Construction Of The Main Tower Pier Caissons For The Greenville Bridge In Mississippi - F. Keith Jacobson (Deep Foundations Institute, 2007)
To be involved in the construction of a deep dredged caisson for a major bridge pier is one of the most rewarding and professionally challenging experiences one can have in the bridge construction business. That experience was doubled in the construction of the two deep dredged caissons for the Highway 82 Bridge over the Mississippi River near Greenville, Mississippi. The challenges and the construction risks associated with constructing these two dredged caisson pier foundations highlight the construction engineering innovation associated with major bridge pier construction. The 1,378-foot Main Span of the Highway 82 Bridge makes it the longest cable stayed bridge span over the inland rivers of the United States. The main piers for this bridge are supported on two dredged caissons measuring 80-feet by 122-feet in plan, founding 200-feet and 170-feet below the river surface. The challenges of constructing these caisson structures, sinking them through 70-feet of water to the river bottom and then excavating and further sinking them to the founding grade without exceeding the design tolerances, were enormous. The construction engineering opportunities for innovation included major breakwater structures to create a friendly environment in 11 fUsec currents, the first time use of Articulated Concrete Mattresses for river bottom scour control, unique air dome design to maximize the buoyancy of the caisson structure while floating, a caisson guide system to assure positive control and positioning of the caisson during the initial sinking phases. and a comprehensive sinking plan to assure maximum control and minimum risk. Many of the innovative solutions to the construction challenges on this bridge will be incorporated into future caisson construction projects on the lower Mississippi River.